Time-Resolved Characteristics of Soft X-Ray and Hard X-Ray Emitted from Nitrogen and Neon Gas Mixtures in 4 kJ Plasma Focus Device - Roomi, Afshin (2011)
Plasma focus (PF) is a pulsed plasma producing device which consists of two coaxial electrodes separated by an insulator sleeve, a vacuum chamber filled with working gas at low pressure, and an electrical circuitry. Upon discharging a capacitor bank, a plasma column is created in nanosecond rise time. The Lorentz force accelerates the plasma sheath along the anode towards the anode tip and compressed magnetically to form a dense plasma column. As a result of electrons interaction with atoms of the anode and working gas, Soft X-rays (SXR) and hard X-rays (HXR) are produced. The effects of applied voltage, operating pressure and working gas composition on SXR and HXR emitted from a 4 kJ plasma focus device which is called ‘APF’ have been investigated. Nitrogen (N2) and Nitrogen: Neon (N2: Ne) admixture with three volumetric ratios of (90: 10), (75: 25), and (50: 50) were used as the working gas in order to study the effect of gas composition on X-ray emission from the device. To investigate the effect of applied voltage and operating pressure on the behavior of SXR and HXR emissions, four voltages of 10, 11, 12, and 13 kV with a range of pressures of 1.5, 2, 2.5, 3, 3.5, 4,4.5, and 5 torr were applied. The diagnostic devices employed during the experiments were a scintillation detector for HXR detection, an array of five filtered PIN-diodes for SXR detection with different energies, a Pin-hole camera with two different filtered apertures for analyzing the dense plasma column, a Rogowski coil for measuring the discharge current, a voltage probe to measure the tube voltage and four oscilloscopes for getting the signals obtained by the different detectors. The results of HXR signals obtained by the scintillation detector showed that the intensity of HXR decreases with an increase of neon gas in the working gas admixture. On the other hand the signals obtained by three PIN-diodes filtered by Al + Mylar (12μm), Al + Mylar (24 μm), and Be (230 μm) which were for SXR, illustrated that the intensity of SXR increases with an increase of neon percentage in the admixture. Also the signals detected by two PINdiodes covered by Al + Mylar (150 μm), and Cu (10 μm) which are for HXR, were in agreement with the results of the scintillation detector. For all compositions of the working gases, it was observed that the intensity of both SXR and HXR increased with increase of the applied voltage. For applied voltages used on every working gas, the optimum pressures for maximum intensity of SXR and HXR emitted were obtained. The results showed that the optimum conditions for maximum emissions of SXR and HXR using nitrogen (N2) and neon (Ne) mixture are different. Therefore, it was found that the APF is in the optimum condition either for SXR or HXR emission. Our results concluded that the mixing neon (Ne) and nitrogen (N2) as the working gas in the APF is a power source of SXR emission.